2010
DOI: 10.2298/jsc100126124f
|View full text |Cite
|
Sign up to set email alerts
|

A study of new antimalarial artemisinins through molecular modeling and multivariate analysis

Abstract: Artemisinin and 18 derivatives with antimalarial activity against W-2 strains of Plasmodium falciparum were studied through quantum chemistry and multivariate analysis. The geometry optimization of the structures was realized with the Hartree-Fock (HF) theory and 3-21G basis set. Maps of molecular electrostatic potential (MEP) and molecular docking were used to investigate the interaction between the ligands and the receptor (heme). Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…This is in agreement with recent literature theoretical findings,25 where it has been suggested that an electrophilic attack of the heme Fe 2+ could occur through the involvement of the endoperoxide linkage. The main in‐crystal Φ ( r ) MM‐EXP minimum amounts to −143(19) kcal mol −1 and is closer to the O4 (1.432 Å from the minimum) than to the O3 atom (1.531 Å).…”
Section: Resultssupporting
confidence: 93%
“…This is in agreement with recent literature theoretical findings,25 where it has been suggested that an electrophilic attack of the heme Fe 2+ could occur through the involvement of the endoperoxide linkage. The main in‐crystal Φ ( r ) MM‐EXP minimum amounts to −143(19) kcal mol −1 and is closer to the O4 (1.432 Å from the minimum) than to the O3 atom (1.531 Å).…”
Section: Resultssupporting
confidence: 93%
“…A comparison of the reported QSAR models on the artemisinin analogues [53][54][55][56][57] and the GRNN model developed in this work is given in ▶ table 4. Although, the calculated descriptors were not similar in the reported works, this comparison reveals the ability of GRNN to predict the activity of artemisinin analogues.…”
Section: Resultsmentioning
confidence: 99%
“…This information is transformed and encoded for lots of problems chemical, pharmacological and toxicological studies on the relationship between structure-activity, quantitative structure-activity and structure-property (SAR, QSAR and QSPR) [79]- [81]. Ferreira et al [82] studied artemisinin and 18 derivatives with antimalarial activity against W-2 strains of Plasmodium falciparum through quantum chemistry and multivariate analysis. The geometry optimization of structures was realized using the Hartree-Fock method and the 3-21G** basis set.…”
Section: Application Of Hartree-fock Methods Using Computational Toolsmentioning
confidence: 99%